Northern Bobwhite Nest Site Selection in Field Borders - Danielle J. Berger; Jessica N. Piispanen; Tim F. Ginnett; Jason D. Riddle (National Quail Symposium Proceedings, 2017)
Field borders are used to supplement early successional habitat critical for northern bobwhite (Colinus virginianus) nesting that is lost to modern intensive agricultural practices. The suitability of field border habitat for nesting may be affected by microhabitat characteristics at the site and patch scale and placement relative to various land-cover types at the landscape scale. We sought to determine whether bobwhite select nest locations at site, patch, and landscape scales. We collected microhabitat data (stem density, percent cover, and ground composition) and distance to land-cover type data (woody edge, crop, ditch, and road) from 26 bobwhite nests and 26 control sites in field borders in North Carolina, USA, during 2010 and 2011. We modeled nest site selection by comparing nests with random locations using conditional logistic regression at the site scale and logistic regression at the combined patch–landscape scale. We performed model selection using the small sample Akaike’s Information Criterion (AICc). The top site-scale model showed that bobwhite selected for the presence of woody cover and avoided open soil at the nest. There was no clear top model at the combined patch–landscape level. In an agriculture-dominated landscape, managers should focus on microhabitat characteristics of field borders to improve suitability for bobwhite nesting.
Keywords: colinus virginianus; northern bobwhite; field borders; nest selection; North Carolina